2022
DOI: 10.3389/fimmu.2022.971428
|View full text |Cite
|
Sign up to set email alerts
|

CMTM6 and CMTM4 as two novel regulators of PD-L1 modulate the tumor microenvironment

Abstract: The tumor microenvironment (TME) plays crucial roles in regulating tumor occurrence, progress, metastasis and drug resistance. However, it remains largely elusive how the components of TME are regulated to govern its functions in tumor biology. Here, we discussed how the two novel functional proteins, chemokine-like factor (CKLF)-like MARVEL transmembrane domain-containing 6 (CMTM6) and CMTM4, which involved in the post-translational regulation of PD-L1, modulate the TME functions. The roles of CMTM6 and CMTM4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 130 publications
0
5
0
Order By: Relevance
“…Evidence indicates that immune cells play an important role in tumor development, metastasis, and drug resistance [ 17 ]. We further explored the relationship between SERPINE1 and tumor immune cells.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence indicates that immune cells play an important role in tumor development, metastasis, and drug resistance [ 17 ]. We further explored the relationship between SERPINE1 and tumor immune cells.…”
Section: Resultsmentioning
confidence: 99%
“…CMTM6 functions as a novel regulator of PD-L1 expression by stabilizing the PD-L1 protein and inhibiting its ubiquitination. [ 9 , 18 ] Its high expression has been closely associated with the occurrence and progression of various cancers, including CRC. [ 19 ] The findings of this study indicate that high CMTM6 expression is a common molecular feature in patients with CRC and is closely correlated with the development of CRC.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, tumour growth in KRAS-transformed cell xenografts was reduced by reducing SLC7A11 transformation and tumorigenicity and increasing glutathione synthesis [41,42]. Moreover, it has been revealed that the p53 gene may inhibit the development of cancer by triggering ferroptosis and limiting SLC7A11 expression [43,44].…”
Section: Interrelationship: Tme With the Development Of Ferroptosis I...mentioning
confidence: 99%